HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra (1967)
A black and white photo of the Heart's Delight Band playing their instruments. Jimmy Bishop, Stan Reid, George Reid, Edmund Worthman, Edwin Legge.